Impacts on Biogenic Carbon Dioxide Emission Fluxes Driven by Generated Numerical-Downscaled Climate Scenarios - San Jose, Roberto; Perez-Camanyo, J. L.; Jim, Miguel (European Journal of Sustainable Development, 2024)
The aim of this research is to analyze the local impacts (high spatial resolution) of tier 1 CMIP6 climate scenarios (SSP126, SSP245, SSP370 and SSP585) on CO2 biogenic emission fluxes after downscaled climate data over five European regions (national, regional and urban scale) for the period: 2015-2050 using numerical simulations with the WRF/Chem-VPRM tool. VPRM is the Vegetation Photosynthesis and Respiration Model which is coupled with the Weather Research and Forecasting (WRF) model and Chem (Transport). Satellite data is used to derive vegetation indexes used by the VPRM model. The effect of climate is isolated using 2018 (reference year) emissions and land use over the entire simulation period and it is calculated as results of the future simulations minus present (2018). The research is part of the European DISTENDER project, who develops a methodological framework to bring together adaptation and mitigation strategies against the risks of climate change. The increase in temperature leads to higher CO2 emissions from vegetation, as the increase in temperature favors the respiration process of plants. The impacts are spatially and temporally varied and therefore each case study and scenario has its own pattern, with a strong influence on the existing vegetation and local climate Keywords: Climate change, CO2, biogenic emissions, scenarios, downscaling